Description of a new ventrite-femoral stridulatory system in the subtribe Hylobiina (Coleoptera: Curculionidae: Molytinae: Molytini) - Mendivil-Nieto, Julián Alexander; Morrone, Juan J. (Zootaxa, 2025)
Stridulation is the most common method of sound production in Coleoptera, with approximately 17 types recognized across more than 30 families. In this study, two types of ventrite-femoral stridulatory systems are identified and described within the subtribe Hylobiina, distinct from those known in Coleoptera and other Curculionidae. System type 1 is associated with the genus Heilus Kuschel 1955, while system type 2 is found in a group of species within the genus Heilipodus Kuschel 1955. The species Heilus spinipennis comb. nov., is transferred from Heilipodus to present system type 1. Finally, the differences in the ventrite-femoral stridulatory system known for various taxa of Curculionidae are discussed.